Formulasi Strategi Bertahan PT Garuda Indonesia Pada Masa Pandemi COVID-19 Tahun 2021 - Charles AN; M. Midhat (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
Coronavirus Disease 2019 or what is often referred to as COVID-19 which began to enter Indonesia in early March 2020. To prevent its transmission, policies such as work from home, social distancing and Large-Scale Social Restrictions (PSBB) were issued. The problem that is being faced by Garuda Indonesia is a very drastic decline in passengers and IATA predicts that the impact of the COVID-19 pandemic will end in 2024. The aim of this study is to analyze and determine the internal and external factors of PT. Garuda Indonesia and Analyzing Porter's Five-Forces Model and PESTEL. The method used is a qualitative method and the tools that the authors use to analyze using the SWOT analysis method, Porter's Five-Forces Model and PESTEL analysis. The time of the research starts from December 2020 to August 2021. From the results of this study, it can be seen that there are four alternative strategies including downsizing as an alternative strategy with the first priority and the total attractiveness value of (6.73), Related Diversification as an alternative strategy with second priority with a total attractiveness value of (5.82), Divestment as an alternative strategy with a third priority with a total attractiveness value of (4.17) and Liquidation as the last alternative strategy with a total attractiveness value of (3, 71).